2010
DOI: 10.1002/edn.152
|View full text |Cite
|
Sign up to set email alerts
|

Family support and conflict among adults with type 2 diabetes

Abstract: Background:Family relationships can be a source of support for people with diabetes and may influence self-management behaviour. Research examining diabetes-related family support and conflict to date has focused on children and adolescents with type 1 diabetes. Aims: To develop a short (≤10-item) measure of diabetes-related family support and family conflict suitable for use among adults with type 2 diabetes, and to evaluate the psychometric properties of this measure in a pilot study. Methods: Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Guell (2011), for her part, identified that familial influence is significant for diabetes self-management. Several studies also suggest that the family can be a social support in encouraging self-care endeavors (Kang et al, 2010) or be a barrier by being nonsupportive (Paddison, 2010). This result may be attributed to the idea that social, emotional, physical, spiritual, and mental aspects of health are interrelated.…”
Section: Number Of Chronic Illnesses and Social Supportmentioning
confidence: 83%
“…Guell (2011), for her part, identified that familial influence is significant for diabetes self-management. Several studies also suggest that the family can be a social support in encouraging self-care endeavors (Kang et al, 2010) or be a barrier by being nonsupportive (Paddison, 2010). This result may be attributed to the idea that social, emotional, physical, spiritual, and mental aspects of health are interrelated.…”
Section: Number Of Chronic Illnesses and Social Supportmentioning
confidence: 83%
“…According to some studies self-management behaviour is influenced by the type of support system the patient has. 9 , 21 , 22 ‘Individuals are more likely to adhere to their diabetic health regimen if they have social support’. 23 The number of respondents who believed in Christianity outweighs other religions and non-believers.…”
Section: Discussionmentioning
confidence: 99%
“…The family and significant others play an important role in the management of diabetes. The person’s family can provide support and practical help for self-management (Albright, Parchman, & Burke, 2001; Chlebowy, Hood, & LaJoie, 2010; Paddison, 2010; Weiler & Crist, 2009). Previous studies have found that support from the partner significantly correlates with treatment adherence and metabolic control (Tang, Brown, Funnell, & Anderson, 2008; Toljamo & Hentinen, 2001; van Dam et al, 2005).…”
mentioning
confidence: 99%